PS1 - 160 A Telephone Based Cognitive Assessment Tool for Brain Metastases Patients. (18th October 2016) - Tsao, M.N.; Edelstein, K.; Bernstein, L.J.; Wong, J.; Laperriere, N.; Perry, J.R.; Sahgal, A.; Menard, C.; Soliman, H.; Chow, E.; Barnes, T.; Danjoux, C.; et al.
Abstract : Improving neurocognitive outcomes following treatment for brain metastases have become increasingly important. We propose that a brief telephone-based neurocognitive assessment may improve follow-up cognitive assessments in this palliative population. Aim: To prospectively assess the feasibility and reliability of a telephone based brief neurocognitive assessment compared to the same tests delivered face-to-face. Methods: Brain metastases patients to be treated with whole brain radiotherapy (WBRT) were assessed using a brief validated neurocognitive battery at baseline, at 1 month and 3 months following WBRT (in person and over the phone). The primary outcome was feasibility and inter-procedural (in person versus telephone) reliability. The secondary objective was to evaluate the change in neurocognitive function before and after WBRT. Results: Out of 39 patients enrolled, 82% of patients completed the baseline in-person and telephone neurocognitive assessments. However, at 1 month, only 41% of enrolled patients completed the in-person and telephone cognitive assessments and at 3 months, only 10% of patients completed them. Results pertaining to reliability and change in neurocognitive function will be updated. Conclusion: The pre-defined definition of feasibility (at least 80% completion for face to face and telephone neurocognitive assessments) was met at baseline. However, a large proportion of participants did not complete either telephone or in person neurocognitive follow-up at 1 month and at 3 months post-WBRT. Attrition remained a challenge for neurocognitive testing in this population even when a telephone-based brief assessment was used.